Characterization of Zika virus binding and enhancement potential of a large panel of flavivirus murine monoclonal antibodies - Willis, Elinor; Hensley, Scott E. (Virology (New York, N.Y.), 2017)
Zika viruses (ZIKVs) are circulating in parts of the world endemic for other flavivirus infections. Some cross-reactive antibodies (Abs) elicited by prior flavivirus exposures can bind to ZIKV and enhance infection of Fc receptor-bearing cells. Here, we measured ZIKV binding of 54 murine monoclonal Abs (mAbs) elicited by exposure with Dengue virus and West Nile virus antigens. We found that 8 of 54 mAbs recognized the envelope protein of ZIKV in conventional binding assays. These 8 cross-reactive mAbs have different specificities; most recognize the DI/II region of the envelope protein but one mAb recognized the DIII lateral ridge of the envelope protein. Interestingly, only 3 of these cross-reactive mAbs were able to enhance ZIKV infection in vitro, and enhancing potential was not strictly correlated with relative binding ability. These data suggest that the ability of flavivirus Abs to enhance ZIKV is dependent on multiple factors.